Cytokine-induced killer cell therapy-associated idiopathic thrombocytopenic purpura: rare but noteworthy. (September 2016) - Fu, Xiaomin; Zhang, Yong; Gao, Quanli; Lin, Jizhen; Zhang, Qinxian; Xu, Benling; Song, Yongping
Idiopathic thrombocytopenic purpura (ITP) is characterized by a diminished platelet count, an autoimmune condition with antibodies against platelets and an increased tendency to bleed. The association between ITP and solid tumors is uncommon. Cytokine-induced killer (CIK) cell therapy is a well tolerated and promising cancer treatment with minimal toxicity. For the first time, CIK cell therapy was reported to be followed by ITP. The mechanism through which CIK induces ITP remains unclear. Imbalanced ratio of Th cells, decreased numbers or impaired function of Treg cells and excessive secretion of cytokines inducing abnormal activation of B cells may be among the possible reasons. Therefore, a better understanding of this rare condition will require further investigation of these cases.